Pengaruh Pendidikan Pasangan dalam Pengambilan Keputusan Bersama Mengenai Pendidikan Anak: Bukti dari Indonesia Timur - Avia, Zahra; Salim, Prasetya Rahman (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2023)
The implementation of joint decisions in households is one of the efforts to realise gender equality and women's empowerment. Previous research has found that a woman's education affects her probability of implementing joint decisions in the household. This study wants to see whether spouse characteristics, namely education, are also a factor in realising the implementation of joint decisions. Using IFLS East 2012 to look at the Eastern part of Indonesia, our multinomial logistic regression results found that spouse education has a positive correlation in increasing the probability of households implementing joint decisions on decisions related to children's education. Other factors such as women's education, place of residence, and working status are also found to be correlated with the probability of households implementing joint decisions.